3D bioprinting in orthopedics translational research. Issue 13 (2nd September 2019) - Zheng, XuanQi; Huang, JinFeng; Lin, JiaLiang; Yang, DeJun; Xu, TianZhen; Chen, Dong; Zan, Xingjie; Wu, AiMin
Abstract: The repair of critical-size bone defect remains a challenge for orthopedic surgeons. With the advent of an aging society and their accompanying chronic diseases, it is becoming more difficult to treat bone defects, especially large segmental bone defects that are caused by trauma, tumors, infections, and congenital malformations. New materials and technologies need to be developed to address these conditions. 3D bioprinting is a novel technology that bridges the biomaterial and living cells and is an important method in tissue engineering projects. 3D bioprinting has the advantages of replacing or repairing damaged tissue and organs. The progress in material science and 3D printing devices make 3D bioprinting a technology which can be used to create various scaffolds with a large range of advanced material and cell types. However, in regard to the widespread use of bioprinting, biosafety, immunogenicity and rising costs are rising to be concerned. This article reviews the developments and applications of 3D bioprinting and highlights newly applied techniques and materials and the recent achievements in the orthopedic field. This paper also briefly reviews the difference between the methods of 3D bioprinting. The challenges are also elaborated with the aim to research materials, manufacture scaffolds, promote vascularization and maintain cell viability.